Sustainable agriculture practices for a resilient future: A review - Naga Harsha Vardhan Peddi; Akhila Badavath; Akkamahadevi Naik; Kavuri Kalpana (Environment Conservation Journal)
The practice of subsistence farming initially emerged in combination with technical advancements that significantly increased agricultural productivity via the use of chemicals and machines. Unfortunately, unanticipated environmental problems like chemical residues, degraded soil, and the accumulation of nutrients in streams resulted from these approaches' quick adoption. The ecosystems and human well-being have suffered greatly as a result of these issues. The 21st century will see a move toward more sustainable agricultural methods that strike a balance between ecological preservation and productivity as a result of increased environmental concerns. Sustainable agriculture refers to management practices that cooperate with natural processes in order to manage all resources sustainably, minimize waste and its effects on the environment, prevent problems, and promote agroecosystem resilience, self-regulation, evolution, and steady growth for the benefit and fulfillment of all. This review primarily explores various sustainable agricultural practices and their impact on the environment. The results of this study will be useful in determining the optimal agricultural practices to boost output while protecting the environment.